The Influence of Technology, Policy, and Environmental Awareness on Energy Efficiency and Conservation in Industrial Estates in Tangerang City - Khamaludin Khamaludin; Eko Sudarmanto; Erlin Dolphina; Loso Judijanto (West Science Nature and Technology, 2023)
This research investigates the intricate interplay between environmental awareness, policy compliance, technology adoption, and energy efficiency and conservation within the dynamic landscape of the Tangerang City Industrial Estate. Leveraging a quantitative approach, the study surveyed 150 participants to analyze the relationships among these key variables. The results reveal significant and positive associations, indicating that organizations fostering environmental consciousness, adhering to energy-related policies, and embracing advanced technologies exhibit heightened levels of energy efficiency and conservation. The structural model's robust fit, assessed through various indices, underscores the reliability of the identified relationships. The findings offer valuable insights for policymakers, industry stakeholders, and researchers seeking to promote sustainability in industrial practices.